Analisis Kemampuan Kognitif Siswa Sd Melalui Media Video Pembelajaran Youtube: Analysis Of Cognitive Ability Of Elementary Students Through Youtube Learning Video Media - Nur Fazriya Masfufa; Enik Setiyawati (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
In the current era, learning activities in schools require teachers to use innovative learning media, teachers in schools often use communication tools as a tool to assist learning activities in class, there are many learning media used by teachers, one of which is YouTube learning video media. With the existence of YouTube learning video media, it makes it easier students understand the material provided and can instill students' cognitive abilities on theme 6 (energy sources and changes) in class III. The purpose of this study was to describe and analyze students' cognitive abilities through the media of YouTube learning videos in class III SDN Gedangan. Researchers use descriptive qualitative research methods, with the type of case study research where researchers can understand and search for cases and look for these results. From the data on the cognitive ability test results of class III students at SDN Gedangan obtained the following scores: obtaining a score of 100 with a percentage of 38%, a score of 96 with a percentage of 41%, a score of 92 with a percentage of 15% and a score of 88 with a percentage of 5%. From the average student overall score data, it is known that the percentage is 96.42% of the overall score of students' cognitive ability test scores. Where this figure is included in the "very good" category. Based on the results of the study, it can be concluded that the use of YouTube learning video media can improve the cognitive abilities of class III students at SDN Gedangan.